Padrões globais de co-ocorrência e interações agonísticas em donzelinhas (Pomacentridae) - Freitas, Rafaella Nunes Palma de (2022)
Coral reefs retain the greatest marine biodiversity, and sustain a wide variety of fish species that interact in multiple ways. Damselfishes are amongst the most conspicuous reef fish, and are notable for their territorial and aggressive behavior, which often leads to competitor dominance and low coexistence probability between damselfish species. However, the degree to which the territorial behavior of damselfishes influences patterns of co-occurrence and agonistic interactions is unknown. It is also unknown how biological traits and phylogenetic distance are related to the agonistic interactions of the Pomacentridae family and if these traits can explain the distribution patterns of damselfishes better. We elucidate these aspects using a global dataset of eight sites representing a gradient of species richness and phylogenetic relatedness between fish. To understand the drivers of agonistic interactions we used a Path Analysis and to understand the agonistic interaction’s structure and which were the central species in each site we used the out-degree centrality metric. Our results showed that the main driver of co-occurrence of damselfishes was the phylogenetic distance (most distant species cooccur more frequently) (P= 0.55), while the agonistic interactions were driven mainly by the co-occurrence of damselfishes (P= 0.74). Besides this, the damselfishes from the Stegastes genus were the central species in the agonistic interactions network in six of the eight sites of our study, representing their territorial behavior and elevated interactions frequency. Our study helps to improve our knowledge about the relationship between co-occurrence and agonistic interactions and to understand the structure of agonistic interactions of the Pomacentridae family, adding to what is already known about these species' role in the reef ecosystem.